"N-carboxymethyl chitosan in differential flotation ofgalena and chalcopyrite" - Yahui Xiang; Kaioeng Wang; Qi Liu (International Mineral Processing Congress, 2014)
"In the differential metal sulfide ore flotation it is desirable to replace the toxic inorganic depressants with environmentally benign chemicals. Chitosan, as a natural and non-toxic polymer, has been proven to be an efficient depressant for chalcopyrite while allowing galena to be floated by xanthate collectors. However, the poor solubility of chitosan limits its potential applications as the flotation could only be carried out at about pH 4 where chitosan is soluble. A carboxymethyl derivative of chitosan, named N-carboxymethyl chitosan (N-CMC), was synthesized by substituting the amino groups of chitosan with carboxymethyl groups. The substitution significantly improved the solubility of chitosan. The structure of N-CMC was studied and compared with chitosan via Fourier transform infrared spectroscopy (FTIR). Flotation tests were performed on single minerals and mineral mixtures (with weight ratio of 1:1) with the addition of appropriate amount of potassium ethyl xanthate (KEX) and N-CMC. The solution pH was varied from neutral to alkaline. The flotation concentrates and tailings were collected and analysed for the contents of copper and lead. FTIR measurements showed that new peaks of C=O stretching of -COOH and N-H deformation of -NH- appeared in N-CMC, which indicated that the carboxymethyl groups were introduced and the amino groups were the sites for the substitution. Flotation results indicated that N-CMC could depress either chalcopyrite or galena depending on the pH. The results were not affected by the sequence of KEX and N-CMC addition. Therefore, N-CMC is potentially useful in Cu-Pb sulfide separation following a bulk Cu-Pb flotation. The N-CMC was also found to have surface cleaning functions, and was able to remove contaminating copper ions from galena surfaces. Therefore, its application in sulfide ore flotation is expected to be more robust than the original chitosan."